2010
DOI: 10.1007/s00213-010-1961-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of childhood abuse and recent stress on serum brain-derived neurotrophic factor and the moderating role of BDNF Val66Met

Abstract: RationaleRecent findings show lowered brain-derived neurotrophic factor (BDNF) levels in major depressive disorder (MDD). Exposure to stressful life events may (partly) underlie these BDNF reductions, but little is known about the effects of early or recent life stress on BDNF levels. Moreover, the effects of stressful events on BDNF levels may in part be conditional upon a common variant on the BDNF gene (Val66Met; RS6265), with the Met allele being associated with a decrease in activity-dependent secretion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 44 publications
2
85
0
1
Order By: Relevance
“…The BDNF Val66Met polymorphism is functional, with the Met-allele resulting in reduced activity-dependent secretion of BDNF (Egan et al, 2003). Stress has been found to compound the effects that the BDNF Met-allele has on BDNF levels, resulting in increased anxiety and depression (Gatt et al, 2009;Elzinga et al, 2011). Indeed, Met-allele carriers have been found to be more sensitive to childhood abuse than Val-carriers, which could result in later psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…The BDNF Val66Met polymorphism is functional, with the Met-allele resulting in reduced activity-dependent secretion of BDNF (Egan et al, 2003). Stress has been found to compound the effects that the BDNF Met-allele has on BDNF levels, resulting in increased anxiety and depression (Gatt et al, 2009;Elzinga et al, 2011). Indeed, Met-allele carriers have been found to be more sensitive to childhood abuse than Val-carriers, which could result in later psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Though nascent, the literature examining this topic suggests that early-life stress and BDNF genotype may interact to result in depression [120]. A recent study of 1,435 adults with a history of MDD reported that the experience of recent life stressors is associated with decreased levels of BDNF [121]. This is consistent with research on murine models of early-life stress, in which a depressed phenotype in rats experiencing early maternal separation is associated with a decrease in mossy fibre development and neurogenesis in the hippocampi of these animals [111].…”
Section: Neurobiological Factorsmentioning
confidence: 99%
“…1 Thus, maltreated children with the serotonin transporter (SERT) genotype conferring low levels of the SERT molecule (5-HTTLPR S allele carriers) seem to have an increased risk for depression compared to maltreated children with the 5-HTTLPR L/L genotype. 1,2 Similar 2-way (gene × environment) interactions between the BDNF Val66Met polymorphism and childhood maltreatment have also been described in the context of other mental health outcomes, [3][4][5] particularly depression. [6][7][8] Synergies between the serotonin (5HT) and BDNF systems have been suggested to contribute to the regulation of the develop ment and plasticity of neural circuits involved in the origin of affective disorders.…”
Section: Introductionmentioning
confidence: 70%